Prevalence of Intestinal Protozoan Parasites and Associated Risk Factors among School Children in Merhabete District, Central Ethiopia - Nigus Dagne; Amir Alelign (Journal of Parasitology Research)
Background. Intestinal protozoan parasitic infections remain one of the major public health problems in tropical regions especially, among developing countries such as Ethiopia. However, no enough epidemiological data is available in this respect in many parts of the country. Hence, this study was aimed at assessing the prevalence of intestinal protozoan parasitic infections and their associated risk factors among school children in Zeita village, Merhabete District, North Shewa Zone, Central Ethiopia. Methods. A cross-sectional parasitological survey was conducted from January to March 2020. A total of 280 children from Zeita primary school were selected using stratified random sampling techniques. Stool samples were collected and examined using direct wet mount, Formal-Ether concentration and Modified Zeihel-Neelsen staining techniques. Results. The overall prevalence of intestinal protozoan parasitic infection was found to be 46.8% (131/280). The three predominant protozoan parasites detected in this study were Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum which were observed in 70 (25.2%), 54 (19.3%), and 7 (2.5%) of the study participants, respectively. Sociodemographic characteristics of the study subjects such as family occupation (P=0.028), sources of drinking water (P=0.001), water handling practice (P=0.027), habit of eating vegetable (P=0.001), and presence of latrine were observed to be significantly associated risk factors for the occurrence of human intestinal protozoan parasites. Conclusion. A high prevalence of intestinal protozoan parasitic infection which has been contributed by different risk factors was revealed in this study. The findings suggested a need of collaborative effort among the educational and health authorities to control the infection in the study area.